#### Answer

(6,5)

#### Work Step by Step

Our two equations are:
1. y=(2/3)x+1
2. 2x+3y=27
First, lets multiply the first equation by 3. We get
1. 3y=2x+3
2. 2x+3y=27
Since we have a 3y in the second equation, we can substitute the first equation into the second equation for 3y. We get the equation:
2x+(2x+3)=27
Simplify this further:
4x+3=27
Subtract 3 and divide by 4 on both sides. Then, we get the value of x:
x=6.
Now that we have the x value, lets find the y value by substituting 6 for x in the first equation.
y=(2/3)(6)+1
Simplify further:
y=5
Therefore our answer to the system of equation is (6,5)